Albendazole nanocrystals in experimental alveolar echinococcosis: Enhanced chemoprophylactic and clinical efficacy in infected mice - Pensel, Patricia Eugenia (2018)
Human alveolar echinococcosis is caused by the fox tapeworm Echinococcus multilocularis and is usually fatal if left untreated. Medical treatment with albendazole (ABZ) remains an effective option. However, due to its low aqueous solubility, ABZ is poorly and erratically absorbed following oral administration resulting in low drug levels in plasma and liver distribution. Thus, there arises the need to find a simple, efficient and scalable method to produce new ABZ formulations with increased bioavailability. Bearing this in mind, ABZ nanocrystals (ABZ-NCs) appears to be a useful tool to achieve this goal. The aim of the current study was to investigate the chemoprophylactic and clinical efficacy of an ABZ-NC formulation on mice infected with E. multilocularis. In the chemoprophylactic efficacy study, mean weight of the cysts recovered from the ABZ-NC group was 50% lower than that recorded from untreated mice, whereas the treatment with ABZ suspension did not show preventive effect. The viability of protoscoleces isolated from ABZ-NC treated mice was significantly lower than control groups. In the clinical efficacy studies, both ABZ formulations resulted in a reduction in the mean weight of the cysts obtained from mice, however only the treatment with the nanosuspension revealed significant differences (P < 0.05) compared to the control groups. Treatment with ABZ-NCs reduced the weight of the cysts by 77% and the viability of their protoscoleces to 34%. All these results coincided with the tissue damage determined at the ultrastructural level. The enhanced chemoprophylactic and clinical efficacy of ABZ-NCs observed in this study could be attributed to an increase in the oral bioavailability of the drug. In a next step, we will characterize the cyst concentration profile after the administration of ABZ-NCs in mice infected with E. multilocularis.